A Bibliometric Analysis of Customer Engagement : Evidence From Hospitality Industry - Zulkifli Musannip Efendi Siregar; Deden Rudy Mustafa; Yayuk Yuliana; Guntur Syahputra (CV. ITTC INDONESIA, 2026)
Customer engagement is one of the most important factors to achieve positive hospitality performance. Several studies related to customer engagement in the hospitality industry have been conducted by several researchers, but research with bibliometric analysis in the hospitality sector is still rare. This bibliometric analysis research aims to map research trends related to the field of customer engagement in the hospitality sector. Data were collected from the Scopus database, with the keywords